Târîh-i Râşid Efendi ; târîh-i Çelebizâde Efendi - İbrâhim Müteferrika, 1670?-1747. (Kostantiniyye [İstanbul])
4 c. 3 c. te (1. c. [29] s., 277 varak ; 2. c. [17] s., 194 varak ; 3. c. [5] s., 114 varak, [10] s., 158 varak)